Evidence of pathogenicity of a mutation in 3′ untranslated region causing mild haemophilia A - El Maarri, O. (2016)
Introduction Despite the high mutation detection rate, in a small group of haemophilia A patients, using current screening methods, no causal mutation in F8 can be detected. In such cases, the causal mutation might be in the non-coding sequences of F8. Aim Rarely, mutations in non-coding sequences reveal a pivotal role. Here, we analysed a mild haemophilia A patient harbouring a mutation in the 3′ untranslated region (UTR) of F8 and elucidated the molecular mechanism leading to haemophilia phenotype. Methods To find the causal mutation, the complete F8 genomic region was analysed by next generation sequencing. The effect of the identified alteration on F8 expression was evaluated in silico and analysed for the splicing effect at mRNA level. Moreover, in vitro studies using a luciferase reporter system were performed to functionally analyse the mutation. Results We identified an alteration in the 3′ UTR (c.*56G>T) as the only change in F8 gene. Pedigree analysis showed a segregation pattern for three affected members for the presumptive mutation. Moreover, the variant was predicted in silico to create a new donor splice site, which was also detected at mRNA level, resulting in a 159 bp deletion in 3′ UTR of F8. Finally, the variant showed reduced expression of the gene reporter firefly luciferase in cell line expression analysis. Conclusion Our results advocate the patient specific c.*56G>T base change in the 3′ UTR to be a disease-associated mutation leading to alternative splicing explaining the mild haemophilia A phenotype.